Optimization of seed enhancement methods on seed germination and emergence of St. John’s wort - M. Nemati Khoei; A. Abbasi Surki; S. Fallah (علوم و فناوری بذر ایران, 2018)
Optimizing the best methods to enhancement of seed germination and early seedling growth of Hypericum perforatum L. an experiment was conducted in Shahrekord University in two stages. In the first stage, a factorial experiment was done in a randomized complete block design with four replications in seed science and Technology lab, Faculty of Agriculture. Treatments consisted osmopriming with PEG in five levels (0, -3, -6, -9 and -12 bar) as first factor and application of GA in four levels (0, 500, 1000 and 1500 ppm) as second factor. results showed that PEG -12 bar + GA 1000 ppm with an average of 91.5% ranked the highest percentage of germination which had no significant difference with PEG -9 bar + GA 1500 ppm and PEG -9 bar + GA 1000 ppm respectively with the germination percentage average 88 and 88.5%, while the control seed with an average (53.5%) had the lowest percentage of germination. As well as combination treatments PEG -9 bar + GA 1000 ppm increased seedling length, seedling dry weight and seed vigor and increased them respectively as by as 1.19, 1.3, 1.96 and 2.14 times than control. The second experiment was conducted in a randomized complete block design with three replications in the research greenhouses conditions, and treatments consisted of the best treatments of first experiment and control. In greenhouse conditions osmopriming PEG -12 bar and application of  GA 1000 ppm with an average of 82% ranked the highest percentage of emergence which had better performance than the control with an average of 41.33 %.  Finally to enhance seed performance of medicinal plant Hypericum perforatum L., it could be recommended osmopriming with PEG -12 bar and application of GA 1000 ppm or PEG -9 bar + GA  1000 ppm.